2010
DOI: 10.1016/j.jmwh.2009.05.009
|View full text |Cite
|
Sign up to set email alerts
|

“Midwives Are Nice, But …”: Perceptions of Midwifery and Childbirth in an Undergraduate Class

Abstract: To promote midwifery among this population, advocates should continue public education efforts through a variety of media and communication strategies, with an emphasis on the safety of midwifery care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…Further, the mechanisms by which magazine article content may have affected women's intentions for birth (which were found to account for a large proportion of the variance in women's change in intentions for a medicalized birth) were also considered in the development of messages contained in the magazine articles, and specifically assessed to allow us to identify those associated with the effect on women's intention for birth. The findings of this study extend the limited literature on young people's attitudes and beliefs about childbirth (DeJoy 2010;Lampman and Phelps 1997;Palumbo et al 2012;Stoll et al 2009Stoll et al , 2013Wallach and Matlin 1992) although several limitations warrant consideration.…”
Section: Strengths Limitations and Future Directionssupporting
confidence: 72%
See 1 more Smart Citation
“…Further, the mechanisms by which magazine article content may have affected women's intentions for birth (which were found to account for a large proportion of the variance in women's change in intentions for a medicalized birth) were also considered in the development of messages contained in the magazine articles, and specifically assessed to allow us to identify those associated with the effect on women's intention for birth. The findings of this study extend the limited literature on young people's attitudes and beliefs about childbirth (DeJoy 2010;Lampman and Phelps 1997;Palumbo et al 2012;Stoll et al 2009Stoll et al , 2013Wallach and Matlin 1992) although several limitations warrant consideration.…”
Section: Strengths Limitations and Future Directionssupporting
confidence: 72%
“…Their attitudes and intentions about birth represent the next generation of maternity care norms and social expectations. Few studies have examined attitudes toward birth in young women who have not yet had children, and those have only studied American and Canadian samples (DeJoy 2010;Lampman and Phelps 1997;Palumbo et al 2012;Stoll et al 2009Stoll et al , 2013Wallach and Matlin 1992). The results of these studies have suggested that the majority of young women lack general childbirth knowledge, and knowledge of caesarean and vaginal birth procedures or their associated outcomes.…”
Section: Expectations Perceived Risk and Attitudesmentioning
confidence: 99%
“…Students associated childbirth with fear and pain, and most viewed in-hospital physician-led births as 'safe' [20]. Similar findings were reported by DeJoy (2010) who found that many US college students considered childbirth as inherently dangerous and unpredictable, and requiring medical intervention [21]. Rink (2012) assessed the impact of the US reality show 'One Born Every Minute' on college women's perceptions of childbirth [22].…”
Section: Introductionmentioning
confidence: 64%
“…the number of participants attending the class and consultant psychologist), mobilization, strengthening the relationship between mothers and staff and the role of the instructor are involved. De Joy (2010) found similar results about obstetricians and labor in studying students’ beliefs (30). Several studies have shown that space and equipment and access to training facilities play an important role in learning, and that psychotherapy training programs for pregnancy problems is also effective in relieving mental issues (31, 32).…”
Section: Discussionmentioning
confidence: 78%